Conselho Municipal de Saúde de Cuiabá : um estudo da participação dos representantes dos usuários na gestão 2014-2016 - Maciel, Soraia Pinto Tamberi Rodrigues (2016)
The present dissertation has as study object the Municipal Health Council of Cuiabá - MT, management 2014-2016, and it looked to identify the institutional competences of the Council and to analyze in which measured the participation of the counselors of the segment of the users influence in the process of formulation, social control and execution of the health politics for the municipality. The problem of the research is circumscribed on the participation of the users in the Municipal Health Council of Cuiabá, the acting of the counselors, the interference in the quality of the public health policies, the relations established between the segments of the users and the Executive Power. It presents the hypothesis that: the functioning of the Municipal Health Council, as regards the process of democratization of the relations of the State with the civil society, has historically been cast through practices that reveal hegemony of the executive power in relation to the users segment. The practice of the counselors, the handling play of the Executive Power and the lack of capacitating appointed by them does not achieve an effective participation. The study, based on theoretical formulations of the dialectical historical materialism, allowed a critical understanding of the political, economical, social and cultural relations, revealing the contradictions, identifying the appearances and how they hide the essence of the reality inside this space, where there is observed the play of force that is established, especially between the segment of the users and the Executive Power. The methodological procedures of this work were orientated by the qualitative approach; as the nature it is a descriptive study. And, as for the proceedings, it is a case study, where we investigate the Municipal Health Council of Cuiabá, with focus in the representative counselors of the users. The results show up some efforts, many difficulties and limitations in the exercise of the participation. The users are revealed shy, little bit question the proposals and directed deliberations and, therefore, they still did not occupy his proper place in this space; it perceived the need for empowerment of the representative counselors of the users, so that the demands of the popular segments are attended in his real necessities, regarding the policies of public health.